Reproduction of Lake Trout Morphotypes at Isle Royale in Northern Lake Superior. Issue 2 (4th March 2017) - Goetz, Frederick; Sitar, Shawn; Jasonowicz, Andy; Seider, Michael
Abstract: The reproductive biology of male and female lean, siscowet, redfin, and humper Lake Trout Salvelinus namaycush was assessed by measuring the gonadosomatic index (GSI) and by histological analysis of the gonads over 2 years from spring to fall at sites surrounding Isle Royale National Park, Lake Superior. Whole livers, otoliths, and ovaries were also collected to measure hepatosomatic index (HSI), age, and fecundity. In general, GSIs increased from spring to summer in male and female siscowets, leans, redfins, and humpers, and this was accompanied by a large increase in the number of vitellogenic (>2.0 mm) follicles in females. Postspawned ovaries and regressing testes were predominant in all morphotypes by October but were also observed in September, indicating that some spawning occurred at least by September. Further, preovulatory siscowet females (GSIs > 10) and siscowet males with fully mature and even regressing testes were observed in the spring and summer, indicating that spawning occurs at least in the spring and fall in siscowets at Isle Royale. For all morphotypes, average male HSIs were significantly lower than female HSIs. Absolute fecundity was positively related to size and age for all morphotypes. Humpers had the lowest absolute fecundity. Leans, redfins, and siscowets had similar fecundity relationships. The results conclusively demonstrate that deepwater siscowet Lake Trout reproduce at least during the spring and fall at Isle Royale and that leans, humpers, and redfins reproduce during the fall. In lakes that exhibit sympatric populations of deepwater and shallow-water ecotypes of Arctic Char Salvelinus alpinus, the deepwater form also spawns in both spring and fall. Our data and those on Arctic Char suggest that there is an adaptive strategy for maintaining alternative spawning times in the deepwater ecotypes in these populations. Received June 20, 2016; accepted November 2, 2016 Published online January 31, 2017